The Study of Causality of Teacher’s Turnover Intention at Private Junior High School - Hardianto, Eddy Setyanto, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose: Identify the direct effect of reward, motivation and job satisfaction on the turnover intention the teacher. Design/methodology: This study used a quantitative approach with a survey method. The data was taken by using questionnaire and analyzed by using path analysis. The research sample was 149 private junior high school teachers in Rokan Hulu District. The sample were taken by using simple random sampling technique. Findings: The results of the study showed that the reward has a direct negative effect on turnover intention. Motivation has a direct negative effect on turnover intention, job satisfaction has a direct negative effect on turnover intention. Research limitations/ implications: The research sample was taken from schools in Rokan Hulu Regency, therefore it is necessary to be careful to generalize the results of this study in a wider scope such as for the province or a country.Practical implicaations: Based on the results of the study, it was known that to reduce teacher turnover intention private junior high school can be done by increasing their reward, motivation and job satisfaction.